Βιβλιοκρισία:Subseciva Groningana X. Studies in Roman and Byzantine Law. In Honour of Roos Meijering, ed. by D. PENNA - F. BRANDSMA - Th. E. van BOCHOVE, Groningen 2019 - ΤΑΝΤΑΛΟΣ Μαριος (Byzantina Symmeikta, 2020)
Subseciva Groningana X. Studies in Roman and Byzantine Law. In Honour of Roos Meijering, ed. by D. Penna - F. Brandsma - Th. E. van Bochove, Groningen 2019